2012
DOI: 10.1111/j.1365-2788.2011.01501.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of caring for adults with intellectual disability on the quality of life of parents

Abstract: Caring for an adult with ID had both positive and negative effects on parents' QOL. Improving services and service delivery, including the provision of residential services and respite, would address many of the issues that were reported to have a negative impact on parents' QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 41 publications
(84 reference statements)
5
32
0
6
Order By: Relevance
“…Deriving satisfaction from the caregiving role is a consistent finding in the literature. For example, Yoong & Koritsas () found that caring had a positive impact on quality of life by enabling participants to develop relationships and receive support, participate in leisure activities, achieve a sense of personal satisfaction and enable a more positive appraisal of their lives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deriving satisfaction from the caregiving role is a consistent finding in the literature. For example, Yoong & Koritsas () found that caring had a positive impact on quality of life by enabling participants to develop relationships and receive support, participate in leisure activities, achieve a sense of personal satisfaction and enable a more positive appraisal of their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Older parents' experiences of depression, stress and anxiety in their caregiving role can be mediated by the high levels of satisfaction associated with caring for an adult‐child with intellectual disabilities (Hill & Rose ; Dillenburger & McKerr ; Rowbotham et al . ; Yoong & Koritsas ). Other factors affecting the psychological well‐being of older parents include availability of support networks, cognitive appraisals of their caregiving roles (Hill & Rose ), taking on additional caregiving recipients (Perkins & Hayley ) and the challenging behaviour of the person with intellectual disabilities (Unwin & Deb ).…”
Section: Introductionmentioning
confidence: 97%
“…; Samuel et al . ; Yoong & Koritsas ). For the authors of these studies, satisfaction with the support services is solely one of many indicators to measure parents' quality of life.…”
Section: Introductionmentioning
confidence: 98%
“…Traditionally, parents' views and experiences have rarely been the focus of studies, despite the widespread knowledge in the scientific literature, of the importance of offering quality services centred on the child and the family's needs. In recent research, parent's satisfaction with the support services is evaluated and measured using a broad concept of quality of life (Olsson & Hwang 2008;Rillotta et al 2012;Samuel et al 2012;Yoong & Koritsas 2012). For the authors of these studies, satisfaction with the support services is solely one of many indicators to measure parents' quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research on parents of adults who have a learning disability tends to focus upon mothers (Yoong & Koritsas, ), and therefore, issues that are father‐specific rarely arise. Of the father‐specific research, much is over 10 years old which limits currency, and studies that include fathers of adults aged 18 and over are often cross‐sectional, focus upon psychological well‐being and employ a quantitative methodology (Davys, Mitchell, & Martin, ).…”
Section: Introductionmentioning
confidence: 99%